Quality of Reporting in Upper Gastrointestinal Endoscopy: Effect of a Simple Audit Intervention - Lisboa-Gonçalves,Pedro (2019)
Background and Aim: In contrast to colonoscopy, there are few studies regarding upper gastrointestinal (UGI) endoscopy reporting its quality and ways of improving it. Quality audits are recommended, but their influence on the abovementioned quality is not well studied. Our aim was to evaluate the quality of UGI endoscopy reports and assess the effect of a simple audit intervention on UGI endoscopy reporting quality. Methods: This was a prospective study in a tertiary referral center, including the evaluation of 1,000 consecutive reports of UGI endoscopies before an audit intervention and 250 after. The reports were analyzed according to performance measures defined by three experienced gastroenterologists. Results: Before the intervention, 51.8% of the incomplete endoscopies did not present any justification for its incompleteness and 88.1% of lesions were correctly described. Overall, 64.1% of the reports were considered as being of high quality. After the audit intervention, follow-up recommendation (53.4 vs. 80.8%, p = 0.001), correct lesion description (88.1 vs. 95.8%, p = 0.001), and correct segment description (92.2 vs. 96.4%, p = 0.020) improved significantly. The rate of unjustified incomplete endoscopies decreased significantly (51.8 vs. 28.9%, p = 0.010). The highquality endoscopy rate improved 13.9% after the intervention (p < 0.001). Both specialists and residents improved with the audit intervention with a similar percentage of improvement in the high-quality endoscopy rate (13.9 vs. 13.4%). Conclusions: A simple audit intervention is a good way to improve the quality of reporting of UGI endoscopy, independently of degree and experience. Some of the performance measure accomplishments may depend on the software used by the endoscopy centers and it should be a priority to optimize it.